Human Semenogelin 1 Promotes Sperm Survival in the Mouse Female Reproductive Tract - Sakaguchi, Daiki (Int J Mol Sci, 2020)
Semenogelin 1 (SEMG1), a main component of human seminal plasma, is a multi-functional protein involved in the regulation of sperm motility and fertility. SEMG1 is orthologous to mouse seminal vesicle secretion 2 (SVS2), required for sperm survival in the female reproductive tract after copulation; however, its in vivo function remains unclear. In this study, we addressed this issue by examining the effect of recombinant SEMG1 on intrauterine mouse sperm survival. SEMG1 caused a dose-dependent decrease in mouse sperm motility, similar to its effect on human sperm, but SVS2 had no effect on mouse sperm motility. Mouse epididymal sperm in the presence of 100 µM SEMG1, a concentration that does not affect mouse sperm motility, were injected into the mouse uterus (intrauterine insemination, IUI). IUI combined with SEMG1 significantly increased the survival rate of intrauterine mouse sperm. The effect of SEMG1 on intrauterine sperm survival was comparable with that of SVS2. For clinical applications, three potentially sperm-protecting polypeptides that are easy to handle were designed from SEMG1, but their individual use was unable to mimic the ability of SEMG1. Our results indicate that SEMG1 has potential clinical applications for effective IUI and thereby for safe, simple, and effective internal fertilization.